IMPLEMENTING DESIGN THINKING METHODE IN DIGITAL-BASED LEARNING INNOVATION TO FACE THE ERA OF SOCIETY 5.0 - Qomariyah, Nuril; Maula, Diah Hadiyatul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Industrial technology currently continues to develop and has entered the era of society 5.0, this also has an impact on the education sector. This development requires innovation in the education sector to be able to face the various challenges that arise. The aim of this research is to analyze and describe the implementation of design thinking in digital-based learning innovation to face the era of society 5.0. The research method used is descriptive qualitative with literature study (library research). In the Design Thinking Method there are five stages, namely, Emphatize, Define, Ideate, Prototype, and Test. These stages are then implemented in digital-based learning innovations. The results obtained in this research indicate that the design thinking method can be used as an appropriate method for teaching staff in developing digital-based learning innovations that are representative in the era of society 5.0.